Cerebral Arterial Pulsatility and Global White Matter Microstructure Impact Spatial Working Memory in Older Adults With and Without Cardiovascular Risk Factors - Alexander C. Conley; Frini Karayanidis; Frini Karayanidis; Frini Karayanidis; Todd A. D. Jolly; Todd A. D. Jolly; Todd A. D. Jolly; Meng-Heng Yang; Meng-Heng Yang; Meng-Heng Yang; Shulan Hsieh; Shulan Hsieh; et al. (Frontiers in Aging Neuroscience, 2020)
Aging is associated with an increased prevalence of vascular health conditions that are linked to a disruption in the cerebral vasculature and white matter microstructural organization. In people with cardiovascular risk factors, increased cerebral arterial pulsatility is associated with poorer white matter microstructural organization and cognitive functioning. This study examines the relationship among arterial pulsatility, white matter microstructural organization, and cognitive ability in a healthy adult lifespan sample. One hundred and eighty-nine adults were divided into a younger adult (<50 years, n = 97) and older adult (>50 years, n = 92). The latter were further subdivided into two subgroups with (CV+, n = 25) and without (CV−, n = 67) cardiovascular risk factors. Arterial pulsatility was measured using cardiac-gated phase-contrast flow quantification sequence and three indexes of whole-brain white matter microstructural organization [i.e., fractional anisotropy (FA), radial diffusivity (RaD), mean diffusivity (MD)] were derived from diffusion-weighted imaging (DWI). Cognitive ability was assessed using global cognitive functioning (MoCA) and a measure of working memory [sensitivity (d′) from a 2-back task]. Neither the whole group analysis nor the younger adult group showed an association between measures of arterial pulsatility, global white matter microstructural organization, and cognition. In older adults, higher MD and RaD were associated with increased arterial pulsatility and poorer working memory performance. The indirect pathway from arterial pulsatility to working memory performance via both MD and RaD measures was significant in this group. Interestingly, a comparison of CV+ and CV− subgroups showed that this mediating relationship was only evident in older adults with at least one CV risk factor. These findings are consistent with cardiovascular risk factors as underlying arterial, white matter, and cognitive decline in cognitively normal older adults.